Candidate genes involved in metastasis of colon cancer identified by integrated analysis - Yiming Zhou; Yiwen Zang; Yi Yang; Jianbin Xiang; Zongyou Chen (Cancer Medicine)
Abstract Colon cancer is one of the most malignant cancers worldwide. Nearly 20% of all colon cancer patients are diagnosed at stage IV (metastasis). However, further study of colon cancer is difficult due to a lack of understanding of its pathogenesis. In this study, we acquired high–throughput sequence data from TCGA datasets and performed integrated bioinformatic analysis including differential gene expression analysis, gene ontology and KEGG pathways analysis, protein–protein analysis, survival analysis, and multivariate Cox proportional hazards regression analysis in order to identify a panel of key candidate genes involved in the metastasis of colon cancer. We then constructed a prognostic signature based on the expression of REG1B, TGM6, NTF4, PNMA5, and HOXC13 which could provide significant prognostic value for colon cancer.